Distribution and utilization of homestead windbreak Fukugi (Garcinia subelliptica Merr.) trees: an ethnobotanical approach - Bixia Chen; Hikaru Akamine (BMC, 2021)
Abstract Background Garcinia subelliptica (Fukugi in Japanese) is an evergreen tropical tree, first identified in Batanes, the Philippines, which has been planted as a homestead windbreak and in coastal forests extensively on the Ryukyu Archipelago, Japan. This article focuses on the traditional uses and cultural values of Fukugi trees and provides ethnobotanical information for the conservation scheme of this important tree species. Methods A combination of ecological and ethnobotanical approaches was applied in this study. Extensive field surveys were conducted to collect dimensions of relatively large trees, and in-depth interviews with the village leaders and knowledgeable persons were conducted to collect ethnobotanical data. Results Fukugi trees have been primarily planted as homestead or farmland windbreaks. Timber was harvested during difficult times, for example, after WWII, and used for recreational purposes for children or farmers. The fruits were also eaten on some remote islands. Old-growth Fukugi trees are widely found in sacred sites, within cities, and as symbolic trees. The older generations respect Fukugi trees; however, the cultural significance valued by older generation seems to be lacking in the younger generation. We argue that Fukugi is a cultural keystone species in Okinawa, which underpins Ryukyu culture and has transformed islands into a pleasant land, a unique place, and shared identity for the community. Conclusions Fukugi windbreaks provide significant ecosystem services, such as biodiversity in the forest, reducing soil erosion, and spiritual and cultural values. A combination of biophysical environment, as well as tradition and custom, has played an essential role in tree species selection for windbreaks. The positive impacts that anthropogenic activities have had on the sustainability of woody species, namely, the active utilization of tree species, may have enabled the species to sustain. Strategies for protecting old-growth Fukugi trees, in addition to restoration of damaged trees, are needed to improve the sustainable management of Fukugi trees in Okinawa.